THE RELATIONSHIP BETWEEN STUDENTS’ INTEREST AND FAMILY MOTIVATION TOWARDS THE DEVELOPMENT OF AN ENTREPRENEURIAL MINDSET: An Empirical Study Of Students At Dharma Wanita Vocational High School, Gresik - Ima Datul Milah; Susilowati Susilowati; Fitria Hansyah Fatmasari (Yayasan Education and Social Center, 2026)
Fostering an entrepreneurial spirit amongst vocational secondary school (SMK) pupils is one of the efforts to prepare graduates who are not only ready for employment but also capable of creating business opportunities independently. However, the development of students' entrepreneurial spirit still faces various challenges influenced by both internal and external factors. This study aims to analyze the relationship between students' interests and family motivation towards the development of entrepreneurial spirit among students at SMK Dharma Wanita Gresik. The study employed a quantitative approach using a correlational method. The sample comprised 30 students selected using purposive sampling. Data were collected via a Likert-scale questionnaire measuring the variables of student interest, family motivation, and the development of an entrepreneurial spirit. Data analysis was carried out using descriptive statistics, tests of assumptions including normality, linearity, and homogeneity, as well as hypothesis testing using Pearson's product-moment correlation. The results indicate that students' interest has a positive and significant relationship with the development of an entrepreneurial spirit (r = 0.660; p < 0.05), whilst family motivation also has a positive and significant relationship with the development of an entrepreneurial spirit (r = 0.436; p < 0.05). These findings suggest that the development of students' entrepreneurial spirit is linked to the internal factors, namely students' interest, and external factors, namely family motivation. Therefore, schools and families need to collaborate in creating an environment that supports the growth of students' creativity, independence, and entrepreneurial spirit.